When Europe was a prison camp : father and son memoirs, 1940-1941 - Schrag, Otto, 1902-1971; Schrag, Peter (Indiana University Press, 2015)
"In an unusual but compelling approach to storytelling, When Europe Was a Prison Camp, weaves together two accounts of a family's eventual escape from occupied Europe. One, a fictionalized memoir written by the father in 1941; the other, begun by the son in the 1980s, fills in the story of himself and mother, supplemented by historical research. The result is both personal and provocative, involving as it does issues of history and memory, fiction and "truth," courage and resignation. This is not a "Holocaust memoir." The Schrags were Jews, and Otto was interned, under execrable conditions, in southern France. But Otto, with the help of a heroic wife, escaped the camp before the start of massive transfers of prisoners "to the East," and Peter and his mother escaped from Belgium before the Jews were rounded up and sent to Auschwitz. Still, the danger and suffering, the comradeship and betrayal, the naïve hopes and cynical despair of those in prison and those in peril are everywhere in evidence"--